FUNDAMENTAL AND TECHNICAL ANALYSIS AND EXTERNAL FACTORS ON FINANCIAL PERFORMANCE MODERATED BY DIVIDEND POLICY - Susanto, Bambang; Dwijayanty, Rima; Ratnawati, Aryanti (PT. Altin Riset Publishing, 2024)
Financial performance proxied by price to book value (PBV) will be greatly influenced by technical and fundamental factors as well as external factors. Technically for listed or public companies, it will be greatly influenced by the volume and frequency of transactions in the secondary market, while fundamentally it will be influenced by asset growth and the level of balance between the company's debt to equity ratio. External factors from the exchange rate and the Fed's interest rate will bring pressure on financial performance, especially if the exchange rate weakens and the Fed's interest rate rises, of course, financial performance will be affected by the increasingly high cost of capital. In this study, the dividend policy variable is included as a moderating variable to produce more comprehensive research outputs.